2023
DOI: 10.1123/jpah.2022-0609
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Physical Activity Patterns in the 2015 Pelotas Birth Cohort: From Preconception to Postpartum

Abstract: Background: Motherhood has been associated with reduced leisure-time physical activity (LTPA) levels. We aim to assess maternal LTPA patterns from preconception to 4 years postpartum. Methods: The study was developed with mothers from the Pelotas 2015 Birth Cohort, Southern Brazil (n = 4273). LTPA data were self-reported for preconception, antenatal, and 3, 12, 24, and 48 months postpartum. Information on LTPA referring to preconception (3 mo before pregnancy) and each gestational trimester was retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Moreover, preconception PA behaviours can have longlasting effects, potentially influencing not only the immediate future pregnancy but also the health trajectories of future generations [2]. In fact, participation in preconception PA is a significant predictor of continued PA during pregnancy [9,10]. Therefore, the preconception period represents a critical window of opportunity for behaviour change [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, preconception PA behaviours can have longlasting effects, potentially influencing not only the immediate future pregnancy but also the health trajectories of future generations [2]. In fact, participation in preconception PA is a significant predictor of continued PA during pregnancy [9,10]. Therefore, the preconception period represents a critical window of opportunity for behaviour change [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits of being physically active before conception, research indicates that preconception PA behaviour is often suboptimal among women of reproductive age [10,[12][13][14]. Notably, a report published by the Australian government revealed that 78% of women of reproductive age fail to meet the national guidelines, which recommend being active on most, preferably all days, with at least 150 min of moderate to vigorous activity per week [12].…”
Section: Introductionmentioning
confidence: 99%
“…The research featured in the Special Issue draws evidence from both well-established cohort studies that have been ongoing for several decades, and contemporary cohorts established since 2010. These influential studies include the 1970 British Cohort Study, 9 the Australian Longitudinal Study on Women's Health, 10 the Pelotas (Brazil) Birth Cohort studies, 3,[5][6][7][8] the Southampton Women's Survey, 4 the Singapore Preconception Study of Long-Term Maternal and Child Outcomes, 2 and the Sasaguri Genkimon Study. 11 This diversity should be celebrated, as comparing and contrasting evidence from different countries and studies established in different periods is crucial to gain a deeper understanding of current trends and patterns in physical activity, taking into account the evolving social, cultural, and technological landscapes that shape our behaviours in today's world.…”
mentioning
confidence: 99%
“…Not coincidentally, physical activity and women's health have emerged as prominent topics within these studies. 3,4,10 This aspect deserves to be highlighted because comprehending physical activity through the lens of life course should drive us to advance strategies aimed at reducing the non-acceptable disparity in physical activity opportunities between men and women, particularly during the reproductive age. 13 Despite our enthusiasm over the successful publication of these 10 manuscripts, we acknowledge there is still much room for improvement within our research field.…”
mentioning
confidence: 99%